A micro-phenomenological and semiotic approach to cognition in practice: a path toward an integrative approach to studying cognition-in-the-world and from within - Poizat, Germain; Flandin, Simon; Theureau, Jacques (Adaptive behavior, 2023)
The article presents the course-of-experience framework and how it contributes to studying cognition in practice. The aim is twofold: (a) to argue for a phenomenologically and semiotically inspired enactivist approach to practice and cognition in practice and (b) to describe research methods that provide rigorous first-person data in relation to practice—in other words, a view “from within” of practice. Practice is considered to be a relevant unit of analysis for studying cognition-in-the-world and is defined as enacted, lived, situated, embodied, and enculturated. Practice is not viewed as a “context for” but as “constitutive” of the cognitive process itself. This article describes (a) the epistemological foundation and general assumptions of the course-of-experience framework, (b) the associated way of looking at pre-reflective self-consciousness and its relation to practice, (c) the analytical hypothesis derived from Peirce’s semeiotic, and (d) some methodological considerations related to data collection, data processing, and analysis. In the concluding section, we outline the added value of the course-of-experience framework for cognitive science, and we indicate possible directions for further research.